THE IMPACT OF TAX TREATY ON FOREIGN DIRECT INVESTMENT IN INDONESIA - Pungki Yunita Chandrasari (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2021)
The Double Tax Agreement (DTA), better known as the tax treaty, was alleged to have had a major influence in increasing the amount of Foreign Direct Investment (FDI) in Indonesia. This study aimed to determine the effect of tax treaties on FDI in Indonesia. The object of this research was tax treaties between Indonesia with 27 treaty partners in the period 1996 to 2017. The technique used to analyze panel data was multiple regression analysis with Fixed Effect Model approach by using EViews 9. The results showed that the independent variables together affect the FDI in Indonesia. Partially, in the long run, tax treaties have a positive effect on FDI in Indonesia, while in the short and medium term, tax treaties have no effect on FDI in Indonesia. The coefficient of determination shows that the influence of the independent variables on the FDI in Indonesia is 48,45% while the rest is explained by other causes outside the regression model of this study.